Newborn screening for severe combined immune deficiency (technical and political aspects). Issue 6 (December 2015) - Unknown
Abstract : Purpose of review: Newborn screening for severe combined immune deficiency (SCID) has been implemented in more than half of the states in the United States. Despite the success of these programs, numerous challenges remain for implementing newborn screening. The present review will focus on technical, programmatic, and political aspects pertinent to newborn screening for SCID. Recent findings: Recent data from newborn screening in 11 U.S. programs suggest that the birth prevalence of SCID is higher than previous estimates. In addition, a large number of other conditions causing T-cell lymphopenia have been detected. Several European countries have initiated pilot screening for SCID. Significant cost savings for treatment of infants with SCID detected at birth, compared with later in life, has been demonstrated. Published evidence of the favorable cost–benefit ratio for screening supports implementation of universal SCID newborn screening. Summary: SCID fulfills criteria for a condition that should be included in routine newborn screening. Data presented from multiple newborn screening programs in the United States and Europe have shown that high throughput screening of all newborns is cost-effective. Screening improves early detection of this life-threatening condition and follow-up studies have shown a clear improvement in survival for early treatment.